Unraveling the Tectonic Evolution of the Eastern Jiangnan Orogen, South China: Constraints From Basalts of Trace Elements, Nd Isotope, and Geochronology - Jiandong Sun; Xuehui Zhang; Jinsong Lv; Haili Li; Shiru Lin (Island Arc, 2026)
The Jiangnan Orogen has long been recognized as an ideal location for Precambrian geologists to study Neoproterozoic tectonic movements. However, the paleogeographic location of the South China Craton within the Rodinia supercontinent and the associated geodynamic mechanisms remain contentious. This research presents results from Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA‐ICP‐MS) zircon U–Pb dating, whole‐rock geochemistry, and Nd isotopes of early Neoproterozoic Jinshan basalts from the Zhangcun Formation. The basalts, dated at approximately 844 Ma, display a tholeiitic affinity, characterized by high MgO (8.19–13.70 wt.%), moderate TiO 2 (0.89–1.40 wt.%), and positive ε Nd ( t ) values (+ 1.35 to +3.53). Normalized rare earth element (REE) patterns and primitive mantle‐normalized trace element distributions indicate a slight enrichment of light rare earth elements (LREE) and a significant enrichment of large ionic lithosphere elements (LILEs), comparable to E2 basalts from the East Scotia Ridge back‐arc basin. It is suggested that the Jinshan basalts originated from a slightly depleted asthenospheric mantle, combined with recycled slab melt. When integrated with existing regional data, these basalts from the eastern Jiangnan Orogen exhibit notable geochemical anomalies, including elevated LREE and incompatible element ratios, as well as lower ε Nd ( t ) values, in contrast to back‐arc basin basalts from the central Jiangnan Orogen. This study proposes that the observed geochemical disparities between the eastern and central Jiangnan Orogen are attributed to varying degrees of slab rollback within the Yangtze Block during the early Neoproterozoic. Furthermore, evidence from prolonged arc magmatism and extensional tectonics related to slab rollback supports the conclusion that the South China Craton is positioned at the periphery of the Rodinia supercontinent.